Break-up in formation of small bubbles: an energy consideration. (2nd January 2017) - Chu, P.; Waters, K. E.; Finch, J. A.
ABSTRACT: The formation of small bubbles in flotation is usually accomplished by the use of frothers, or sometimes is due to the presence of inorganic salts in the process water. The effective mechanism associated with the presence of these solutes is generally considered to be coalescence inhibition. However, recent work has demonstrated that the presence of frothers and salts also reduces the size of bubble at the initial formation stage. In this paper, we adapt the same experimental setup to investigate the time that it takes for a bubble to form; for a known system power input, the energy to form a bubble can then be estimated from the time. The hypothesis is that the presence of frother and salt will reduce the time for a bubble to form, which can be interpreted as an added energy component being derived from the solute. Testing different types and concentrations of frothers and salts, the hypothesis is supported: the mechanical energy required to form a bubble decreases by about 10% in the presence of these solutes.